Ecological Status of Diospyros melanoxylon in Dry Deciduous Teak Forests of Sagar (Madhya Pradesh) - Prasad, Ram; Mishra, G. P. (Indian Forester, 1980)
In spite of uniform climatic conditions the forests of Sagar are very heterogeneous in composition and quality. The present state of vegetation appears to be the outcome of micro-climatic influences resultiug from variation in geological formations, physiography and biotic interferences.Though, Diospyros melanoxylon like teak and Anogeissus latifolia, out numbers other species in plant density, its ultimate progression to maturity is One of the lowests. This indicates a high degree of mortality mainly due to biotic factors such as grazing, cutting, leaf plucking and fires.Like other tree species; annuals and perennials, Diospyros melanoxylon in dry deciduous teak forests have been provided with the phenomenon of dying back to ensure its survival and subsequent establishment. The dying back in this species appears to last upto 10 years of age beyond which normal all-round growth takes place and plants are established.